2020
DOI: 10.1037/pri0000119
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to enhance communication with telemental health measurement-based care (tMBC).

Abstract: Telehealth has always held great promise to increase access to mental health care, never more so than in the age of COVID-19, when clients cannot or will not come to the clinician's physical location. A feasible and effective alternative to traditional in-person care, telemental health requires that clinicians adopt new strategies to build and maintain communication and the therapeutic relationship. This can be particularly troublesome for clinicians new to the modality, who may feel the loss of the "insession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Há uma grande oportunidade para soluções inovadores em saúde mental, aumentando o número de pessoas que possam obter acesso ao cuidado de qualidade 10,56,57 .…”
Section: Discussionunclassified
“…Há uma grande oportunidade para soluções inovadores em saúde mental, aumentando o número de pessoas que possam obter acesso ao cuidado de qualidade 10,56,57 .…”
Section: Discussionunclassified
“…Telepsychotherapy reduces the risk of infections that people fear, and enables continuous psychotherapy for both clients and psychotherapists in their own safe space (Rosen & Glassman, 2020). There is a skepticism about the formation of therapeutic alliance through telepsychotherapy, but recent studies have shown that it provides an opportunity to improve treatment alliance and empathy (Douglas et al, 2020). It is demonstrated that psychological treatment can be safely provided to clients (Madigan et al, 2020).…”
Section: ⅲ Telepsychotherapymentioning
confidence: 99%
“…In the age of coronavirus where social distancing is mandatory, innovative methods to overcome the barriers of face-to-face psychotherapy are needed, and one of the alternatives is telepsychotherapy (Watts et al, 2020). This approach not only protects psychotherapists and clients from the risk of infection, but also provides a new Jung, Byungho / Sandplay Therapy Performed by Telepsychotherapy: Going Beyond the Limits of Face-to-Face Psychotherapy in the COVID-19 Pandemic -155 -therapeutic opportunity in the sense of communicating in the client's natural field of life (Douglas et al, 2020). In the pandemic era, telepsychotherapy can be one of the key therapeutic approaches, and has been proven that it can be well provided to clients in need of psychotherapy (Perrin et al, 2020).…”
mentioning
confidence: 99%
“…The recent outbreak of the novel coronavirus disease (COVID-19), which was classified as a global pandemic by the World Health Organization in March of 2020, has necessitated clinician use of telehealth strategies to continue serving patients encouraged to stay in their homes as part of efforts to slow the societal spread of COVID-19 (Douglas et al, 2020;Gurwitch et al, 2020;Smith et al, 2020). U.S. Census Bureau data already indicate that the COVID-19 pandemic and associated social distancing measures have had a significant negative impact on the mental health of Americans (see Fowers & Wan, 2020), with many experts hypothesizing that the impact of isolation may exacerbate existing mental health problems, underscoring the urgency for continuity of care (Torales et al, 2020).…”
Section: Homementioning
confidence: 99%